2018
DOI: 10.1097/rct.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Bone Density Measurement on Abdomen and Pelvis Computed Tomography to Predict Fracture Risk in Women Aged 50 to 64 Years Without Osteoporosis Risk Factors

Abstract: Opportunistic bone density screening can identify women at elevated risk of developing fractures within 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…oCT data has been shown to accurately correlate to current and future VCFs with diagnostic accuracy as high as 97.4% and AUC ¼ 0.978. 30,[44][45][46][47] oCT has outperformed DXA in the prediction of VCFs. 23,24 oCT has even been used to screen for cervical spine and hip fractures among the elderly.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…oCT data has been shown to accurately correlate to current and future VCFs with diagnostic accuracy as high as 97.4% and AUC ¼ 0.978. 30,[44][45][46][47] oCT has outperformed DXA in the prediction of VCFs. 23,24 oCT has even been used to screen for cervical spine and hip fractures among the elderly.…”
Section: Resultsmentioning
confidence: 98%
“…Different thresholds have been proposed using receiver operating characteristic (ROC) analysis to optimize sensitivity and specificity ( Table 1 ). 22 , 23 , 25 , 28 - 30 Pickhardt et al 22 found that optimum thresholds for prediction of osteoporosis were less than 100 HU, while normal bone could be considered greater than 150 HU. Among other studies, highly specific HU lower limit thresholds range between 73 and 100, while highly sensitive cutoffs range between 100 and 180 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting masks can be used for the same purposes as those generated with AI-based algorithms Vertebral morphometry and shape analysis [ 32 , 33 ] Classical algorithms to automatically determine vertebral morphometry and shape. Grading of fracture severity [ 34 36 ] Morphological measures to classify vertebra fractures. …”
Section: Vertebral Fracture Assessmentmentioning
confidence: 99%
“…Iodine-containing contrast agents are frequently administered prior to a CT scan in order to increase the contrast of blood-containing vessels and tissues. These contrast agents increase CT values [ 34 , 43 , 44 , 74 , 75 ]. The impact on BMD depends on the amount of contrast agent, i.e., the concentration within the bone of interest at the time of the CT scan.…”
Section: Assessment Of Bmdmentioning
confidence: 99%
“…More recent studies on opportunistic CT have used fractures as outcomes [67][68][69][70][71][72][73][74]. In patients who had a hip fracture after an abdominopelvic CT examination performed for other reasons, Lee et al [73] reported significantly lower L1 trabecular attenuation values (98.5 ± 36.8 HU) in patients who fractured, compared to age-and sex-matched controls (129.7 ± 44.9 HU).…”
Section: The Presentmentioning
confidence: 99%